PROTOTYPE OF INSPECTION EXHAUST BRAKE VEHICLE BASED MICROCONTROLLER - Pramudi, Setia Hadi; Abdillah, Dzikri Putra; Wibowo, Helmi; Suartika, I Made (Teknik Elektro Universitas Siliwangi, 2023)
Technical requirement checking relating exhaust brake on vehicle inspection is still lacking because there is no additional equipment which can helps to ensure the exhaust brake works. From that case a set of research is conducted to help inspectors to ensure the exhaust brake works normallyÂ by using microcontroller based prototype. This research aims to design and implement the inspect equipment of exhaust brake using sound sensor DFr and air Sensor. The process requires 3 inspectors and by using this tool, inspectors could ensure the exhaust brake works or not for hino vehicle. This research shows that measuring by using this auxiliary tool for checking the exhaust brake could inform the fluctuation of sound produced by vehicle machine and decreasing air on exhaust brake system. The result of its prototype testing, the sound sensor is able to detect the increasing of sound and if the sound level reaches 80 dB, there will be a green as warning LED and l2c LCD displays the noise level and the prototype could works properly, the accuracy percentage is 97% and for the air Sensorâ€™s accuracy is 92%